Effect of Feeding Difference Levels of Concentrate on NNH3, VFA and In Vitro Digestibility - Wijayanti, Ni Putu Putri; Cakra, I Gusti Lanang Oka; Mahardika, I Gede (E-Journal of Animal Science Udayana University; Vol 4 No 1 (2015), 2015)
The aim of this research was to observe the effect of giving difference levels concentrate on NNH 3 , VFA production and in vitro of dry matter and organic matter digestibility. Completely Randomized Design (CRD) was used in this study with four treatments and four replications, i.e. 75% concentrate + 25% forage (60% king grass + 40% glyricidia ) (A); 60% concentrate + 40% forage (60% king grass + 40% glyricidia ) (B); 45% concentrate + 55% forage (60% king grass + 40% glyricidia ) (C); and 30% concentrate + 70% forage (60% king grass + 40% glyricidia ) (D). The result of this study showed that the NNH 3 concentration was highest in treatment A, which was 13.60 mM. VFA concentration was higher in treatment C, which was 118.40 mM. Dry matter digestibility and organic matter digestibility was higher in treatment A, which were 59.71 and 60.27%. It is concluded that the giving of concentrate with containing urea, lime and cassava from 30 to 75% has non-significant (P>0.05) effect on NNH 3 and VFA level in every treatments. Giving higher level of concentrate will be increase dry matter and organic matter digestibility